Factors influencing fruit purchase decisions in the Chachapoyas model market: an analysis using structural equation modeling - Barrera-Quispe, Jimena (2024)
The objective of this study is to identify factors influencing product purchase choices in the sample market of Chachapoyas using structural equation modeling (SEM) using AMOS v.24 software. The sample of 384 customers was composed mostly of women (60%) and young people aged 18 to 30 years (55%), and it was found that personal characteristics such as age, lifestyle and financial situation influenced purchase decisions. The results showed that cultural, social and psychological factors did not have a significant effect. The usefulness of SEM for studying the interaction between multiple variables and validating theoretical models in non-experimental settings was confirmed. These findings underscored the importance of considering personal factors in marketing and business strategies in local market settings. The conclusion is that understanding individual characteristics is important for understanding consumer purchase dynamics in the Chachapoyas sample market and provides a solid basis for designing more effective marketing strategies that align with the needs of local consumers.